Analisis perbandingan rencana strategi pada bank lokal di Indonesia - Brillianty, Farizah Auliya; Dewi, Annisa Sinta; Kurniawati, Lina (Maliki Interdisciplinary Journal, 2024)
Banks are financial institutions that function as collectors of funds and distribute them back in the form of credit or what can also be called financing to sharia financial institutions. In a company, be it a bank, there must be a strategic plan to help facilitate the process of achieving company goals. As for every company, including banking, there are definitely differences in strategic planning. Therefore, it is necessary to analyze strategic plans which will determine the differences in strategic plans in each company, especially the following three banks, namely Bank Jatim, Bank BPD DIY, and Bank DKI. The purpose of this analysis is to compare the strategic plans of each bank. This research was conducted using data collection methods through the Central Statistics Agency (BPS), the Financial Services Authority (OJK) and financial reports from each bank which includes information on the bank's strategic plans. The results of the comparative analysis show that Bank Jatim has specific strategic planning for a more effective credit handling plan. Bank DKI explains long-term and short-term strategic plans as well as work plans and budgets. Meanwhile, Bank DIY prioritizes human resources, capital and achievements in their strategic plans.